Development of a highly mobile and versatile large MA‐XRF scanner for in situ analyses of painted work of arts. (22nd July 2020) - Pouyet, Emeline; Barbi, Nicholas; Chopp, Henry; Healy, Owen; Katsaggelos, Aggelos; Moak, Sophia; Mott, Rick; Vermeulen, Marc; Walton, Marc
Abstract : A new portable macro X‐ray fluorescence scanner has been specifically designed for in situ, real‐time elemental mapping of large painted surfaces. This system allows scanning 80 × 80 × 20 cm 3 along the X, Z, and Y directions, respectively, with adaptive beam size at the energy of the Rh Ka‐line. The detection system consists of a 50 mm 2 active area detector coupled to a CUBE pre‐amplifier and to the DANTE digital pulse processor (DPP) with adaptive shaping time. The system is controlled with a custom software including a graphical user interface (GUI) programmed in Python for real‐time control of the stage, DPP, and camera of the scanner. This system allows considering new ways of sampling the object surface than the usual raster scanning in serpentine as well as a live elaboration of X‐ray data; technical details and performances of the scanner are presented in this paper together with an example of its application to investigate painted surface, illustrating the value of the developed instrument.